A Simulation of Liquid Crystal Grating with Field‐Induced Twist Deformation for Beam‐Steering Applications. Issue 2 (11th September 2022) - Park, Sun-Geun; Lee, Ye-Lin; Kim, Wook-Sung; Oh, Seung-Won
Abstract : Beam‐steering device using liquid crystal (LC) grating with field‐induced twist deformation, which has symmetric LC director distribution, is demonstrated. The proposed LC cell can convert the polarizations without multidomain LC alignments, and the polarization of the output light can also be changed with different input polarization. Therefore, the polarization of the input light is controlled, and the polarization of the output light is analyzed by additional layers that each consists of a switchable quarter‐wave plate (QWP) and a linear polarizer. The transmitted light of the proposed LC cell can be diffracted in three different directions by changing the bias voltage. The calculated efficiency and angle of steering are 46% and 8°, respectively. Potential applications of such a grating for diffraction optics, optical interconnect, and beam‐steering devices are foreseeable. Abstract : An beam‐steering device that uses liquid crystal (LC) can control the beam in three directions depending on the applied voltage. To control beam directions, the additional layers act as polarization converter and filter. The device could be used in LiDAR and to fold the optical path in augmented reality.